Theories of Work and Working Today - Okhuysen, Gerardo A.; Lepak, David; Ashcraft, Karen Lee; Labianca, Giuseppe (Joe); Smith, Vicki; Steensma, H. Kevin (Academy of Management Review, 2013)
The article discusses conceptions of work as a focus of research in the area of organization and management. We consider obstacles in the study of work, including different disciplinary lenses used in research. We discuss the contributions of the articles in this special topic forum, as well as questions generated from them. We end by examining how different disciplines may approach new questions about work, and call for an engaged and rich consideration of work as a dynamic phenomenon